STRATEGI PENGEMBANGAN USAHA KERAMBA JARING APUNG DI KOPERASI BONTANG “ETA MARITIM” KOTA BONTANG (Business Development Strategy For Floating Net Cages At The Bontang Eta Maritim Cooperative, Bontang City) - FIKRI IKHSAN WIJAYA; NURUL OVIA OKTAWATI; OON DARMASYAH (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2023)
The purpose of this study was to analyze the business development strategy for floating net cages at the Bontang Eta Maritim Cooperative, Bontang City. Floating net cages are modern fish farming containers and are commonly found in Indonesian waters. This study used a purposive sampling method, collecting primary data using interview and questionnaire techniques. Secondary data was obtained from library sources related to research. Data analysis used descriptive analysis Analytical Hierarchy Process (AHP). Using the AHP method, the priority proposals for marine development strategies for Bontang Eta Maritim cooperatives were obtained by strengthening facilities and infrastructure (0.43), with the alternative provision of seeds (0.60), The second priority that must be strengthened is institutional (0.35), with the alternative of providing technical guidance (0.30), and the last thing that must be strengthened is the priority of human resources (0.22) with the alternative of providing cultivation training (0.55).